Alterations in innate immunity and epithelial cell differentiation are the molecular pillars of hidradenitis suppurativa. (30th January 2020) - Zouboulis, C.C.; Nogueira da Costa, A.; Makrantonaki, E.; Hou, X.X.; Almansouri, D.; Dudley, J.T.; Edwards, H.; Readhead, B.; Balthasar, O.; Jemec, G.B.E.; Bonitsis, N.G.; Nikolakis, G.; et al.
Abstract: Background: The large unmet need of hidradenitis suppurativa/acne inversa (HS) therapy requires the elucidation of disease‐driving mechanisms and tissue targeting. Objective: Robust characterization of the underlying HS mechanisms and detection of the involved skin compartments. Methods: Hidradenitis suppurativa/acne inversa molecular taxonomy and key signalling pathways were studied by whole transcriptome profiling. Dysregulated genes were detected by comparing lesional and non‐lesional skin obtained from female HS patients and matched healthy controls using the Agilent array platform. The differential gene expression was confirmed by quantitative real‐time PCR and targeted protein characterization via immunohistochemistry in another set of female patients. HS‐involved skin compartments were also recognized by immunohistochemistry. Results: Alterations to key regulatory pathways involving glucocorticoid receptor, atherosclerosis, HIF1α and IL17A signalling as well as inhibition of matrix metalloproteases were detected. From a functional standpoint, cellular assembly, maintenance and movement, haematological system development and function, immune cell trafficking and antimicrobial response were key processes probably being affected in HS. Sixteen genes were found to characterize HS from a molecular standpoint ( DEFB4, MMP1, GJB2, PI3, KRT16, MMP9, SERPINB4, SERPINB3, SPRR3, S100A8, S100A9, S100A12, S100A7A (15), KRT6A, TCN1, TMPRSS11D ). Among the proteins strongly expressed in HS, calgranulin‐A, calgranulin‐B and serpin‐B4 were detected in the hair root sheath, koebnerisin and connexin‐32 in stratum granulosum, transcobalamin‐1 in stratum spinosum/hair root sheath, small prolin‐rich protein‐3 in apocrine sweat gland ducts/sebaceous glands‐ducts and matrix metallopeptidase‐9 in resident monocytes. Conclusion: Our findings highlight a panel of immune‐related drivers in HS, which influence innate immunity and cell differentiation in follicular and epidermal keratinocytes as well as skin glands.